Pemanfaatan Kecerdasan Buatan dalam Konstruksi Bahan Ajar: Studi Implementasi Program Kemitraan Masyarakat - Herdi; Syaifullah; Novembli, Meta Silfia; Ahmad, Arif (Puslitbang Sinergis Asa Professional, 2026)
The Community Service Program (PkM) aims to evaluate the effectiveness of artificial intelligence (AI) in the development of teaching materials by teachers. The background of this program is the demand for educational transformation in the digital era, which requires teachers to have adequate digital literacy. The implementation of PkM adopts a practice-based training approach, combining intensive face-to-face sessions with online monitoring through WhatsApp groups. The effectiveness of the program is measured by comparing pre-test and post-test scores, as well as qualitative data analysis from participant observations and discussions. The results of the activity show a significant increase in teachers' knowledge and skills, as evidenced by an increase in scores from the pre-test to the post-test. ChatGPT proved to be effective in facilitating the development of ideas and teaching material frameworks, while Quillbot contributed greatly to improving text quality. In addition, online monitoring revealed teachers' initiatives to explore other applications such as Canva and the formation of strong collaboration among participants. Overall, this program not only succeeded in improving teachers' technical abilities but also built awareness of the importance of technology integration as an integral part of learning strategies. The conclusion of this activity is that the integration of AI in teacher training is effective in improving teaching quality and supporting teachers' professionalism in a sustainable manner.